The impact of exporting and export destination on manufacturing wages: Evidence for sub-Saharan Africa - Chris Milner; Verena Tandrayen (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2004)
Since the late 1980's many Sub-Saharan African governments, under the auspices of the World Bank and IMF, have embarked on substantial reform programmes aimed at liberalising trade and expanding exports. There has been a large literature exploring aggregate export and growth response to trade liberalisation, but relatively little empirical work on the labour market effects of these programmes. This paper seeks to provide insights into the individual wage effects of the trade-status of firms. Specifically, it provides a micro-econometric analysis of the implications for African manufacturing worker's earnings of being employed in an exporting firm. Using a rich employer-employee matched data set for manufacturing firms in six Sub-Saharan countries over the period 1993 to 1995; we find a positive association between individual earnings and the export status of the firm. Moreover, it appears that the skill wage premium in exporting firms is significantly higher. These results are consistent with either trade inducing higher wages, or with more productive (higher wage) firms, self-selecting themselves into export activity. The results also reveal however, that export destination matters and that the wage premium varies across export markets. In particular, exports to competitive markets outside Africa generate a negative export wage premium whereas exporting to the less competitive African market yields a positive effect on wages. This suggests that there is a greater disciplining effect on wages when exporting is to more competitive markets.
Keywords: 330